Atomistic origin of high-concentration Ce3+ in 100-faceted Cr-substituted CeO2 nanocrystals. (15th January 2021) - Hao, Xiaodong; Yoko, Akira; Inoue, Kazutoshi; Xu, Yang; Saito, Mitsuhiro; Chen, Chunlin; Seong, Gimyeong; Tomai, Takaaki; Takami, Seiichi; Shluger, Alexander L.; Xu, Bingshe; Adschiri, Tadafumi; et al.
Abstract: Improving the potential of promising CeO2 -based nanocatalysts in practical applications requires an atomic-scale analysis of the effects of active dopants on the distribution of Ce valence states and the formation of oxygen vacancies ( V O s). In this study, a Cr dopant is introduced into the cubic 100-faceted CeO2 nanocrystals (NCs) with an average size of 7.8 nm via supercritical water. The Cr dopants substitute Ce sites in the amount of approximately 3 mol%. Based on the aberration-corrected STEM-EELS, the effects of Cr dopant on the distribution of cerium valence states are investigated layer by layer across the ultrafine Cr-substituted CeO2 NC perpendicular to the 100 exposed facet. It is found that an increased amount of Ce 3+ cations is present in Cr-substituted CeO2 NCs, particularly in the internal atomic layers, compared to the pristine CeO2 NCs. The atomic-scale analysis of the local structure combined with theoretical calculations demonstrates that Cr dopant reduces the formation energy of V O s and increases the mobility of oxygen atoms for the nano-sized CeO2 . These effects, in principle, result in an improved oxygen storage capacity and provide a fundamental understanding of role of the dopant in the formation and distribution of V O s in the doped CeO2 NCs. Graphical Abstract: Image, graphical abstract